2020
DOI: 10.1186/s13287-020-01948-5
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin suppresses ER stress-dependent proapoptotic effects via AMPK in bone mesenchymal stem cells during mitochondrial oxidative damage

Abstract: Background Bone marrow mesenchymal stem cells (BMSCs) have been used as important cell-based tools for clinical applications. Oxidative stress-induced apoptosis causes a low survival rate after transplantation, and the underlying mechanisms remain unknown. The endoplasmic reticulum (ER) and mitochondria are vital organelles regulated by adenosine monophosphate (AMP)-activated protein kinase (AMPK), especially during oxidative stress injury. Melatonin exerts an antioxidant effect by scavenging f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 62 publications
0
25
0
Order By: Relevance
“…11 Previous studies demonstrated that AMPK activation restored mitochondrial function by maintaining redox status and sustaining mitochondrial membrane potential, which inhibits mitochondria-induced apoptosis. 12 Downstream transcriptional factors dependent on the AMPK signaling axis, such as Nrf2, Sirt1, and Foxo, regulate several genes that reinforce antioxidant defenses. 13-15 Moreover, senescent cells respond to oxidative stress through mitophagy, which is the process of selectively clearing long-lived or fragmented mitochondria.…”
Section: Introductionmentioning
confidence: 99%
“…11 Previous studies demonstrated that AMPK activation restored mitochondrial function by maintaining redox status and sustaining mitochondrial membrane potential, which inhibits mitochondria-induced apoptosis. 12 Downstream transcriptional factors dependent on the AMPK signaling axis, such as Nrf2, Sirt1, and Foxo, regulate several genes that reinforce antioxidant defenses. 13-15 Moreover, senescent cells respond to oxidative stress through mitophagy, which is the process of selectively clearing long-lived or fragmented mitochondria.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that melatonin suppresses ER stress-mediated proapoptotic effects in bone mesenchymal stem cells [29]. Suwanjang W et al suggested that the protective effect of melatonin is mediated via cytosolic calcium in DEX-induced neurotoxicity [30].…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of melatonin in regulating other ocular stem cells, such as corneal epithelial stem cells, and the assessment of their effect in treating ocular diseases in animal models are still unknown. Furthermore, melatonin also exhibits regulating ability for exogenous stem cells such as mesenchymal stem cells (MSCs) in viability, proliferation, differentiation, paracrine, and apoptosis through certain signaling pathways like Wnt and MAPK and acts as antioxidant agents to reduce the oxidative stressā€“induced apoptosis and enhance activity of stem cells ( Ping et al, 2017 ; Chatterji et al, 2018 ; Lee et al, 2018 ; Majidinia et al, 2018 ; Fan et al, 2020 ; Giannaccare et al, 2020 ). Such properties of melatonin have been successfully applied in various disease therapies, including chronic kidney diseases, neurodegenerative diseases, and orthopedic disorders, through pretreatment or combining with scaffold, while its application is rare for ocular diseases ( Ramezani et al, 2020 ; Yan et al, 2020 ; Yoon et al, 2020 ).…”
Section: Toward the Futurementioning
confidence: 99%